(untitled) (Journal of the College of Basic Education, 2023)
Criminal thinking is one of the predictive variables of crime. and crime prediction is important in reducing and controlling it before it occurs. Therefore, the research aimed to identify the criminal thinking of preparatory students. The researcher prepared a scale for measuring criminal thinking (general, proactive, Reactive) consisting of (23) items, according to the theory of criminal thinking styles. Results show that middle school students have low (general, proactive) criminal thinking, and high reactive criminal thinking. There is no difference in general criminal thinking according to sex and economic level, but there is a difference in the interaction between sex and economic level, in favor of males who have a good economic level compared to females of the same level. And there is no difference in proactive criminal thinking according to the variables of sex and economic level, while there is a difference in the interaction between sex and economic level in favor of males who have a good economic level compared to females of the same level, and in favor of females with medium economic level over males at the same level. And there were no differences in reactive criminal thinking according to the variables of sex and economic level, not even in the interaction between them. We conclude that middle school students have a high willingness to engage in crime, if they are provoked, because of their high interactive criminal thinking, and the individual may develop proactive criminal thinking if he does not put an end to it.